Endoscopic Sealing of Bronchopleural Fistulas with Submucosal Injection of a Tissue Expander: A Novel Technique - Cayo García-Polo; Antonio León-Jiménez; Jose Luis López-Campos; Aurelio Arnedillo; Enrique González-Moya; Juan José Fernández-Berni; Juan Manuel Gómez (Canadian Respiratory Journal)
The occurrence of a bronchopleural fistula (BPF) continues to represent a challenging management problem, and is associated with high morbidity and mortality. A novel and successful technique that uses submucosal injection of a tissue expander for bronchoscopic occlusion of BPFs has been designed. This method may be used either alone or in combination with bronchoscopic instillation of n-butyl-cyanoacrylate glue. The occlusion technique is described, with a presentation of two patients who were successfully treated with this method. The submucosal injection of a tissue expander is an effective, economical and minimally invasive technique for managing BPFs.